2019
DOI: 10.3389/fneur.2019.01271
|View full text |Cite
|
Sign up to set email alerts
|

Co-occurrence of Anti-N-Methyl-D-Aspartate Receptor Encephalitis and Anti-myelin Oligodendrocyte Glycoprotein Inflammatory Demyelinating Diseases: A Clinical Phenomenon to Be Taken Seriously

Abstract: Background: Anti-N-methyl-D-aspartate receptor (NMDAR) immunoglobulin G antibodies which exist on myelin sheaths, composed of oligodendrocytes, especially target GluN1 subunits and are highly characteristic of anti-NMDAR encephalitis which is a newly recognized autoimmune encephalitis (AE) characterized by psychiatric symptoms, behavioral abnormalities, seizures, cognitive impairment and other clinical symptoms. Myelin oligodendrocyte glycoprotein (MOG) is a type of protein which is expressed on the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
1
31
0
Order By: Relevance
“…Consistent with previous studies, [ 3 , 25 , 28 , 30 ] symptoms of anti-NMDARe and MOG-ab disease exist independently or overlap sometimes.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with previous studies, [ 3 , 25 , 28 , 30 ] symptoms of anti-NMDARe and MOG-ab disease exist independently or overlap sometimes.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the prevalence of co-existing autoimmune diseases, such as that of autoimmune encephalitis and myelin oligodendroglial glycoprotein antibody disease, has increased in recent years, as indicated by a recent study ( 115 ). In addition, another study has demonstrated that the HLA class II allele DRB1*16:02 is involved in the pathogenesis of autoimmune encephalitis and reported an association between specific HLA class II alleles and autoimmune encephalitis for the first time, thus providing new insights into the pathogenesis of this disease ( 116 ).…”
Section: Discussionmentioning
confidence: 99%
“…The concomitant release of autoimmune antibodies detected in the same patient with an autoimmune disease is not a rare clinical phenomenon. For example, encephalitis associated with MOG antibodies may overlap with N-methyl-Daspartatereceptor (NMDAR) antibodies (20,21); and Jarius reported that concomitant autoimmune disorders were present in 8% of MOG-IgG-positive patients (18).…”
Section: Discussionmentioning
confidence: 99%